Roles of the GLABROUS1 and TRANSPARENT TESTA GLABRA Genes in Arabidopsis Trichome Development. - Larkin, J. C. (1994)
Arabidopsis trichomes are branched, single-celled epidermal hairs. These specialized cells provide a convenient model for investigating the specification of cell fate in plants. Two key genes regulating the initiation of trichome development are GLABROUS1 (GL1) and TRANSPARENT TESTA GLABRA (TTG). GL1 is a member of the myb gene family. The maize R gene, which can functionally complement the Arabidopsis ttg mutation, encodes a basic helix-loop-helix protein. We used constitutively expressed copies of the GL1 and R genes to test hypotheses about the roles of GL1 and TTG in trichome development. The results support the hypothesis that TTG and GL1 cooperate at the same point in the trichome developmental pathway. Furthermore, the constitutive expression of both GL1 and R in the same plant caused trichomes to develop on all shoot epidermal surfaces. Results were also obtained indicating that TTG plays an additional role in inhibiting neighboring cells from becoming trichomes.